Systematic Literature Review : Strategi dalam Meningkatkan Kemampuan Menulis Teks Narasi Berbasis Kearifan Lokal di Sekolah Dasar - Gustina Nasution; Adrias Adrias; Aissy Putri Zulkarnaini (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Learning strategies are very important to be applied in preparation for the implementation of learning in its implementation can be attributed to local wisdom which is a concept that refers to the culture of the surrounding community. This study aims to analyze learning strategies based on local wisdom and its integration with the improvement of narrative writing skills in Indonesian language learning over the last 10 years which have been published in SINTA-indexed journals. This research is a qualitative research using a literature review of 20 articles. The writing of this article is assisted by several applications such as publish or perish and mendeley. Learning strategies can be associated with local wisdom that is adapted to the culture in the local environment. The results of the literature review are in the form of a classification of learning strategies in improving the ability to write narratives based on local wisdom. The results of the analysis show that local wisdom can be integrated into learning models, learning media, and the development of teaching materials. Based on the research, the application of learning strategies based on local wisdom can improve the ability to write narrative texts and can train critical thinking, creativity and cultural literacy.